Is the Taxon of Altaic Languages Natural or Artificial? - Tambovtsev, Yuri (Lingua Posnaniensis, 2010)
The article considers if the taxon of Altaic languages natural enough to call it a good classification. The more compact a taxon, the more natural it is. The article deals with the peculiarities of functioning of labial consonants in the languages of the Altaic language unity and the peculiarities of functioning of labial consonants in subgroups, groups, families and other language taxa of world languages. The analysis is made with the help of such statistical methods as the coefficient of variance, the confidence interval, Chi-square and t-test. The linguistic conclusions on the similarity of functioning of labial consonants are made on the basis of the statistical criteria. It is possible to establish the typological distances between some language taxa (Turkic, Finno-Ugric, Tungus-Manchurian, Slavonic, etc.) on the values of the t-test.